Analisis Pengaruh Pendapatan Perkapita, Pengeluaran Pemerintah Sektor Pendidikan, dan Sektor Kesehatan Terhadap Jumlah Penduduk Miskin di Kabupaten Probolinggo - Wildan Arya Wicaksana; Wiwin Priana Primandhana (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Poverty is a social status where people are unable to fulfill their basic daily needs. Probolinggo Regency has the highest number of poor people and is the fourth highest in East Java Province. For this reason, the role of the government is needed in eradicating the problem of poverty. The aim of this research was to see the relationship between per capita income, government spending in the education sector, and government spending in the health sector on the number of poor people in Probolinggo Regency. Time series data from 2011-2021 is the data used in this study which was obtained from the website of the Central Bureau of Statistics for East Java Province and Probolinggo Regency, the Probolinggo Regency Education Office and the Indonesian Ministry of Education and Culture, as well as the Health Office for East Java Province and Probolinggo Regency. A quantitative approach using multiple linear regression analysis models is the method in this study. The results obtained show that per capita income and government spending on the education sector have a negative and significant effect on the number of poor people in Probolinggo Regency. Meanwhile, government expenditure in the health sector has a negative and insignificant effect on the number of poor people in Probolinggo District.